Improving Adaptive Quality of Service for Multimedia Wireless Networks Using Hierarchical Networks Approach - Kandasamy, Saravanan (2004)
Multimedia traffic is expected to populate the next generation wireless networks. As in wireline networks, the wireless network must able to provide a guaranteed quality of service (QoS) over the lifetime of mobile connections. Some challenging problems such as user mobility, limited frequency spectrum and shortage of bandwidth, influence the QoS provisioning for the users. This thesis examines into the issue of delivering a guaranteed quality of service (QoS) for multimedia services in wireless environment. A PhD candidate, Prihandoko have proposed an Adaptive QoS (AdQoS) model to guarantee the delivery of multimedia services. That work have been adopted and extended by means of a hierarchical network approach, calling it as Improved AdQoS model.The main objective that the Improved AdQoS framework tries to accomplish is to reduce the New Call Blocking Probability (NCBP) and Handoff Call Dropping Probability (HCDP). The key feature of this framework is the integration of the hierarchical network together with the modified Call Admission Control (CAC) algorithm and the bandwidth reallocation scheme. These schemes are developed to control the bandwidth operation of ongoing connections when the system is overloaded depending on the movement speed of a particular user assuming the speed of a mobile user would not be changed throughout the duration of a connection. The performance of the system is evaluated through simulations of a cellular environment under three different scenarios. Scenario A represents an area with 80% slow speed users and 20% fast speed users, Scenario B represents an area with a population of 40% slow speed users and 60% fast speed users while Scenario C represents an area with 20% slow speed users and 80% fast speed users. When compared with the scheme proposed Prihandoko in the literature, the simulation results show that our proposed scheme reduces the new call blocking probabilities, the handoff dropping probabilities and reduces significantly the probability of terminating calls